Pengaruh Model Pembelajaran Sains Teknologi dan Masyarakat (STM) Terhadap Peningkatan Kemampuan Berempati Pada Anak Usia Dini - S Vadilla, Waviq; Hidayanti, Maria; Nurhidayat (Departement of PAI, Universitas Majalengka, 2024)
Empathy is the ability to understand emotions to improve relationships. Empathy is included in affective and cognitive responses, both responses can be developed through the Science, Technology, Society (STS) learning model which is a learning model that brings together Science, Technology, and Society to solve things around the environment. This research is motivated by the following problems: 1) children's ability to care is still low, 2) children have not been able to empathise, 3) the use of learning methods is less interesting. This research aims: (1) to understand the application of the Science, Technology and Society (STS) learning model; (2) to assess the level of children's empathy skills; (3) to evaluate the extent to which the application of the STS learning model affects children's empathy skills. This study involved a population of 15 class A children at RA Al-Wardah, using quantitative analysis methods with a descriptive approach. Data collection techniques through observation, questionnaires, and documentation. The data obtained were analysed with descriptive statistics and product moment correlation. From the research obtained the results of the Science, Technology, Society (STS) learning model in class A RA Al-Wardah is in the development of Beginning to Develop (MB) with a percentage of 37.3%, and the Empathy Ability of class A children at RA Al-Wardah has increased after implementation in the development of Developing Very Well (BSB) previously had a percentage of 16% increased to 18.57%. ANOVA Table data analysis obtained the results of a significance value of 0.829 indicating a linearly distributed value, and product moment correlation analysis techniques with a calculated r value of 0.727 indicating a strong relationship between the STS learning model and Empathy Ability in class A children at RA Al-Wardah.